Stimuli‐responsive crosslinked nanomedicine for cancer treatment. Issue 6 (21st April 2022) - Xue, Xiangdong; Qu, Haijing; Li, Yuanpei
Abstract: Nanomedicines are attractive paradigms to deliver drugs, contrast agents, immunomodulators, and gene editors for cancer therapy and diagnosis. However, the currently developed nanomedicine suffers from poor serum stability, premature drug release, and lack of responsiveness. Crosslinking strategy can be utilized to overcome these shortcomings by employing stimuli‐responsive chemical bonds to tightly hold the nanostructure and releasing the payloads spatiotemporally in a highly controlled manner. In this Review, we summarize the recently ingenious design of the stimuli‐responsive crosslinked nanomedicines (SCN) in the field of cancer treatment and their advances in circumventing the drawbacks of the conventional drug delivery system. We classify the SCNs into three categories based on the crosslinking strategies, including built‐in, on‐surface, and inter‐particle crosslinking nanomedicines. Thanks to the stimuli‐responsive crosslinkages, SCNs are capable of keeping robust stability during systemic circulation. They also respond to the particular tumoral conditions to experience a series of dynamic changes, such as the changes in size, surface charge, targeting moieties, integrity, and imaging signals. These characteristics allow them to efficiently overcome different biological barriers and substantially improve the drug delivery efficiency, tumor‐targeting ability, and imaging sensitivities. With the examples discussed, we envision that our perspectives can inspire more attempts to engineer intelligent nanomedicine to achieve effective cancer therapy and diagnosis. Abstract : We classify the stimuli‐responsive crosslinked nanomedicines (SCNs) into three categories based on the crosslinking strategies, including built‐in, on‐surface, and inter‐particle crosslinking nanomedicines. These SCNs can respond to particular tumoral stimuli and go through a series of dynamic changes to circumvent different biological barriers, and subsequently improve anti‐cancer efficacy and imaging sensitivity and specificity.